2021
DOI: 10.1186/s12889-021-12338-8
|View full text |Cite
|
Sign up to set email alerts
|

Third birth intention of the childbearing-age population in mainland China and sociodemographic differences: a cross-sectional survey

Abstract: Background Global fertility declines have become an inevitable trend, and many countries are adopting policies to drive fertility increases. Fertility intention plays an important role in predicting fertility behavior. The Chinese government has recently issued the ‘three-child’ policy, and there is still little research on the third birth intention of the childbearing-age population. Therefore, the aim of this study is to investigate the prevalence and related reasons of third birth intention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 49 publications
(50 reference statements)
4
22
3
Order By: Relevance
“…This finding is lower than that of Jue Liu who found the second-child intent rate was 39.4% in central and eastern China after the universal two-child policy ( 15 ). Likewise, the third-child intention rate in our survey was also lower than the data obtained nationwide by another scholar in 2021 which was 12.2% ( 14 ). Unlike previous studies ( 10 ), here, we conducted a cross-sectional survey among couples with one child for second-child intention and couples with two children for third-child intention, controls for confounding factors and provides more detail and therefore accuracy ( 19 , 20 ).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…This finding is lower than that of Jue Liu who found the second-child intent rate was 39.4% in central and eastern China after the universal two-child policy ( 15 ). Likewise, the third-child intention rate in our survey was also lower than the data obtained nationwide by another scholar in 2021 which was 12.2% ( 14 ). Unlike previous studies ( 10 ), here, we conducted a cross-sectional survey among couples with one child for second-child intention and couples with two children for third-child intention, controls for confounding factors and provides more detail and therefore accuracy ( 19 , 20 ).…”
Section: Discussioncontrasting
confidence: 68%
“…Fertility intention is regarded to predict fertility behavior and it is affected by government policy as well as individual, social, economic, and cultural factors ( 12 , 13 ). In China, previous studies have shown that the prevalence of the fertility intention was 39.4% for a second child in 2017, and 12.2% for a third child in 2021 among the general population ( 14 , 15 ). According to this year's National Bureau of Statistics, 43% of the births in 2021 were second births.…”
Section: Introductionmentioning
confidence: 98%
“…An alarming finding of this study is that low fertility intentions were reported by our study participants across all the regions in China. A recently published study conducted among the public of child-bearing-age between 31 to 40 years in China reported 12.2% had third birth intention [18]. Further, the 2017 National Fertility Survey reported only 2.2% do not plan to have any children [6].…”
Section: Discussionmentioning
confidence: 99%
“…The aging process together with decreased fertility rate will result in a shrinking workforce and growing health expenditure, which hampers economic and social development ( 12 , 13 ). A three-child policy has just been released on May 31, 2021, in China, however, the third birth intention of the childbearing-age population in China is still low after the announcement ( 14 ). Reversing declined fertility is still a primary concern around the world.…”
Section: Introductionmentioning
confidence: 99%